The impact of aerosols on space-based retrievals of carbon dioxide - Nelson, Robert R., author; O'Dell, Christopher W., advisor; Denning, A. Scott, committee member; Kummerow, Christian D., committee member; Lefsky, Michael A., committee member (Colorado State University. Libraries, 2015)
This work describes an investigation into the impact of aerosols on space-based retrievals of the column-averaged dry-air mole fraction of carbon dioxide (XCO2). It was initially hypothesized that a simplified non-scattering, or "clear sky", retrieval, which neglects scattering and absorption by clouds and aerosols, could potentially avoid errors and biases brought about by attempting to measure properties of clouds and aerosols when there are none present. Clear sky retrievals have the benefit of being orders of magnitude faster and potentially as accurate as "full physics" retrievals that attempt to gain information about clouds and aerosols. Real data from the Greenhouse Gases Observing Satellite (GOSAT) and simulated data from the Orbiting Carbon Observatory-2 (OCO-2) were analyzed to find conditions under which a clear sky retrieval might perform as well as a full physics retrieval. It was found that for real GOSAT data the clear sky retrieval performed relatively well over land but not as well over ocean. The opposite conclusion was found for simulated OCO-2 data: it performed well over ocean but poorly over land. For both real GOSAT data and simulated OCO-2 data, high levels of filtering were needed for the clear sky retrieval to be able to perform nearly as well as or better than the full physics retrieval for both land and ocean surfaces. Spectral residuals were then examined to determine if the clear sky algorithm's performance was tied to errors in the spectral fitting. It was found that the clear sky retrievals had larger residuals than the full physics retrievals but that reducing the clear sky residuals by allowing them to fit for a customized residual pattern did little to reduce the XCO2 errors. It was also shown that even very clear scenes can result in small but detectable clear sky residual patterns. A comparison of cloud and aerosol properties measured by the XCO2 retrieval algorithm to aerosol optical depths from the AErosol RObotic NETwork (AERONET) revealed that the algorithm is generally unable to accurately retrieve information about the amount of clouds and aerosols present. Using OCO-2 simulations, it was shown that the algorithm is also only somewhat able to retrieve the heights of the aerosol layers. Information retrieved about individual aerosol types was shown to be even less accurate. Finally, early work in this study prompted investigation into how sensitive the XCO2 retrieval algorithm is to the first guess of aerosol properties. χ² space was explored by varying the first guess of various aerosol parameters. It was revealed that the retrieved aerosol information and XCO2 values can be highly sensitive to the first guess of the state vector, indicating significant nonlinearity in the retrieval's forward model. Two main conclusions were derived from this work. The first is that an analysis of real GOSAT clear sky XCO2 retrievals and simulated OCO-2 clear sky XCO2 retrievals revealed that the clear sky algorithm is generally inferior to the full physics algorithm, except for when high levels of filtering are applied. The second conclusion is that the current aerosol parameterization leads to unacceptable levels of nonlinearity in the XCO2 retrieval. These results motivate further study to improve the retrieval algorithm's aerosol parameterization, either directly or by including additional information, which may result in an improvement of the retrieval algorithm's ability to accurately measure XCO2.
Keywords: carbon dioxide; aerosols